Wearable Haptic Feedback System for Mitigating Motion Sickness in Autonomous Vehicle Users - AHMAD IZZUDDIN AB HALIM; Abd Fathul Hakim Zulkifli (Progress in Engineering Application and Technology, 2026)
This paper discusses how an autonomous vehicle environment simulated using a wrist-wearable haptic feedback system enhances the individual’s perception of motion and reduces the likelihood of motion sickness. One of the greatest problems with automated driving is motion sickness, as occupants experience a conflict between their senses due to the limited visual and control indicators. The existing countermeasures tend to be pharmacological or visually based, and these countermeasures cannot always be applicable. This paper, therefore, analyzes another intervention, which is a peripheral vibrotactile intervention. The primary goal of this paper is to evaluate the effect of haptic feedback on the sensation of motion sickness and the experience in general. A baseline and haptic group of twelve subjects participated in an instrumented vehicle on-road test, which was a controlled evaluation conducted on the road. Motion sickness was quantified using the Motion Sickness Assessment Questionnaire (MSAQ) as opposed to objective motion exposure, which was read using the Motion Sickness Dosage Value (MSDV). The User Experience Questionnaire (UEQ) was used to assess the user’s perception and acceptance. The statistical tests used in the comparison of conditions included the Welch t-test and the Mann-Whitney U test. The results of these indicate that the stimulus of motion is similar in all tests, and lateral motion is a major contributor to motion exposure. The condition based on the haptic was slightly inclined to generate the low scores on motion sickness, but the statistics did not prove to be significant. However, the UEQ scores indicate that the haptic system is positively accepted and perceived to be usable. The outcomes of this research suggest that the principle of wrist-based haptic feedback may be beneficial as an auxiliary support for motion perception. However, further studies employing a larger sample and more sophisticated feedback designs may enhance its performance.